ANALISIS PENERAPAN AKUNTANSI SYARIAH BERBASIS MUZARA’AH DALAM SISTEM BAGI-HASIL PETANI KECAMATAN KAMANRE - Riska Yanti LK; Nispa Sari Sari; Rifqa Ayu Dasila (Jurnal Riset Terapan Akuntansi, 2026)
This study aims to analyze the implementation of the muzara’ah contract in the agricultural profit-sharing system in Kamanre District, Luwu Regency, and to examine its conformity with the principles of sharia accounting. The research employs a qualitative descriptive method, with primary data collected through interviews and documentation involving farmers and landowners across seven villages in Kamanre District. Data were analyzed through data reduction, presentation, and conclusion drawing. The results indicate that the agricultural profit-sharing system has been implemented effectively based on the principles of justice, trust, and transparency. The profit-sharing ratio is generally two parts for the cultivator and one part for the landowner (2:1), agreed upon by both parties. Although financial recording is still carried out in a simple and traditional manner, sharia accounting values have been naturally applied in the community’s agricultural practices. The implications of this research highlight that the application of sharia accounting based on the muzara’ah contract can serve as a fair and sustainable agricultural partnership model that enhances farmers’ welfare and strengthens social relationships between landowners and cultivators. Keywords: Sharia Accounting, Muzara’ah, Profit Sharing, Agriculture, Justice.